Pengaruh Stress Kerja Dan Emotional Intelligence Terhadap Turnover Intention Internal Auditor - Hermawan Prasetya, Hardi; Ariyanto, Dodik (E-Jurnal Akuntansi, 2019)
The purpose of the study was to analyze work stress and emotional intelligence on the turnover of the intention of internal auditors at PT Bank BRI. The study was conducted in 29 offices at PT Bank BRI Bali-Nusra Region in 2019. The auditor's research respondents were 107. Complementary techniques with saturated sample methods. Data collection was carried out by distributing questionnaires and returning data as many as 96 auditors. Data was tested by multiple linear regression analysis techniques. Based on the results of the analysis, the work stress variable has a significant effect on the auditor's internal turnover intention at PT Bank BRI Denpasar Regional Office with a significance value of 0.000 <0.05, H1 is accepted. Emotional intelligence has a significant effect on internal auditor turnover intention at PT Bank BRI Denpasar Regional Office with a significance value of 0.004 <0.05, H1 is accepted. Keywords : Stress Of Work; Emotional Intelligence; Turnover Intention.